PENGARUH PEMBELAJARAN TAHFIDZ TERHADAP KEMAMPUAN MENGHAFAL SURAH PENDEK DI TK TUNAS HARAPAN 1 BALIKPAPAN - Dwi Nur Rahmawati; Iskandar Yusuf (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of Tahfidz learning on the ability to memorize short surahs among Group B children at TK Tunas Harapan 1 Balikpapan. The study employed a quantitative approach using a survey method. The sample was selected using a saturated sampling (total sampling) technique involving all 80 Group B students. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using IBM SPSS Statistics, including validity testing, reliability testing, normality testing, simple linear regression analysis, coefficient of determination (R²), and t-test. The results showed that Tahfidz learning had a positive and significant effect on children's ability to memorize short surahs. This was evidenced by the t-value of 10.784, which was higher than the t-table value of 1.991, with a significance value of 0.000 < 0.05, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. The coefficient of determination (R²) was 0.599, indicating that Tahfidz learning contributed 59.9% to the ability to memorize short surahs, while the remaining 40.1% was influenced by other factors not examined in this study. Therefore, Tahfidz learning can be considered an effective program for improving the ability of early childhood students to memorize short surahs.